Jawabanmu

2014-04-26T20:51:56+07:00
(sin A + sec A)²+(Cos A+cosec A)²=
=SIN² A+SEC² A+2 SIN A SEC A + SEC² A + COSEC² A+2COSACOSECA
=SIN²A+COS²A+SEC²A+COSEC²A+2(SINASECA+SECACOSECA)
=1+SEC²A+COSEC²A+2(SINA/COSA+COSA/SINA)
=1+SEC²A+COSEC²A+2(SIN²A+COS²A/COSASINA)
=1+SEC²A+COSEC²A+2(1/COSASINA)
=1+SEC²A+COSEC²A+2(1/COSA.1/SINA)
=1+SEC²A+COSEC²A+2SECACOSECA
=(1 + SEC A COSECA)² TERBUKTI
makasih ya ^^
sama2 :)
eh tapi bukannya (1+secA.cscA )^2 = 1+2secAcscA+sec^2Acsc^2A ya?
2014-04-26T21:42:37+07:00
(Sin A + Sec A)² + (Cos A + Csc A)² =
= Sin²A + 2SinASecA + Sec²A + Cos²A + 2CosACsc²A + Csc²A  (dari yg pakai ciri)
=
1 + 2SinA    +  2CosA      +       1
          CosA          SinA      Cos²A    Sin²A
= 1  + 2Cos²A + 2Cos²A  + Sin²A + Cos²A
                SinACosA           Sin²ACos²A
= 1 + 2(Cos²A + Sin²A)    +             1
             SinACosA           Sin²ACos²A
= 1 +        2(1)      +                  1
            SinACosA       Sin²ACos²A
= 1  + 2( 1    .     1  )    +      1    .    1
             SinA  CosA        Sn²A    Cos²A
= 1 + 2CosASinA + Cos²ASec²A
=  (SecACosA)² + 2SinACosA + 1  faktorkan
= (1  +  SecACosA)(1 + SecACosA)
= (1 + SecACosA)²
Jadi terbukti bahwa (SinA + SecA)²  +  (CosA +  CscA) = (1 + SecACscA)²